Pengaruh Laba Bersih, Arus Kas Operasi, dan Investment Opportunity Set (IOS) Terhadap Kebijakan Dividen - Anisa Fitri; Dila Angraini (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This research was conducted to evaluate how net profit, operational cash flow, and IOS influence dividend policy, both individually and simultaneously. This research applies a quantitative approach method in its analysis. The research population consists of property and real estate companies listed on the IDX during the period 2019 to 2023. The sample was determined based on a systematic process using a purposive sampling technique applied by considering special criteria. Data processing and analysis was carried out using the panel data regression method supported by EViews version 12 software. Research findings indicate that partially, net profit and operating cash flow have a significant influence on dividend policy. However, the investment opportunity set (IOS) variable does not show a significant influence on the dividend policy implemented by the company. However, when viewed simultaneously, net profit, operating cash flow, and investment opportunity set (IOS) have a significant influence on dividend policy.